Korelasi Kompetensi Pedagogik dan Motivasi Kerja terhadap Kreativitas Guru Pendidikan Agama Islam Sekolah Menengah Pertama di Kota Jambi - Masyhudi Masyhudi; Musa Musa (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2018)
This study aims to determine: the relationship of pedagogic competence to the creativity of PAI Teachers in junior high schools throughout Jambi; the relationship of work motivation to the creativity of Guru PAI in junior high school in Jambi City; the relationship of pedagogic competence and work motivation to the creativity of PAI Teachers in junior high school all Jambi city together. This research is a quantitative research with correlational approach. The population in this research is all Islamic Religious Education Teachers in junior high school in Jambi City, the sample in this research is 58 teachers. Data collected through questionnaire. Data analysis technique using data normality test analysis, data linearity test, partial correlation test and multiple test. Hypothesis testing using path analysis with significance level a = 0,05. Three conclusions of the research are: 1) there is a positive and significant relationship between Pedagogic Competence with Teacher Creativity with correlation coefficient of 0.728 and contribution 53,1%. 2), a positive relationship between Work Motivation with Teacher Creativity with Coefficient correlation of 0,575 and contribution 31,3%. 3), it was also found positive relationship between Pedagogic Competence and Work Motivation with Teacher Creativity with a correlation coefficient of 0.767 and 58.8% contribution. The conclusion of this research is that there is a relationship between pedagogic competence and work motivation with teacher's creativity in teaching.